Ensiling experiment in bagged silage with 3 silage additives - Lundmark, Cecilia (2006)
The aim with this project was to test the effect of three different silage additives with respect to the chemical quality of the resulting silage. The 3 additives tested were Kofasil Ultra, Kofasil Life and AIV 2S. The additive-treated silages were compared with each other and also with untreated silage (no additive). The experiment was performed on July 22, 2004 at Kungsängen Research Centre in Uppsala. The silage bag that was made had a total length of 48 m and a theoretical diameter of 2.44 m (8 feet). The different additive-treated forages were fed into the bag in approx. 5 m long sections (3 sections/additive). Sections were separated by layers of rolled barley. Unloading was performed during a cold period between Jan. 3rd and Jan 7th, 2005. Samples were cored out with a drilling-machine and analysed with respect to contents of dry matter, ash, sugars (WSC), metabolisable energy, ammonia nitrogen, pH, fatty acids, ethanol and clostridial spores (Clostridium spp.). Acceptable silage quality was produced in the untreated control silages (no additive), but all additive-treated silages were of better quality than the control silages. The best silages qualities were achieved with the additives Kofasil Ultra and AIV 2S.